Immediate enamel bond strength of universal adhesives to unground and ground surfaces in different etching modes. (17th June 2019) - Takeda, Mitsuhiro; Takamizawa, Toshiki; Imai, Arisa; Suzuki, Takayuki; Tsujimoto, Akimasa; Barkmeier, Wayne W.; Latta, Mark A.; Miyazaki, Masashi
Abstract : The purpose of this study was to determine the immediate bond effectiveness of universal adhesives to unground and ground enamel surfaces in different etching modes, through shear bond strength (SBS) tests and scanning electron microscopy observations. Three universal adhesives, a conventional two‐step self‐etch adhesive, and a conventional single‐step self‐etch adhesive were compared. Human enamel specimens from lower anterior teeth were divided into four groups and subjected to the following treatments: (i) unground enamel in self‐etch mode; (ii) ground enamel in self‐etch mode; (iii) unground enamel in etch‐&‐rinse mode; and (iv) ground enamel in etch‐&‐rinse mode. Bonded assemblies were subjected to SBS testing. All the adhesives showed significantly higher SBS values in etch‐&‐rinse mode than in self‐etch mode, regardless of whether enamel was unground or ground. The influence of the enamel surface condition on SBS was different in different etching modes. Without pre‐etching, all tested materials showed lower SBS values in unground enamel than in ground enamel. In etch‐&‐rinse mode, no significant differences in SBS values were observed between unground enamel and ground enamel for any of the adhesives tested. Phosphoric acid pre‐etching before application of self‐etch adhesives to an unground enamel surface is essential to enhance initial enamel bond effectiveness.